2022
DOI: 10.36253/caryologia-1353
|View full text |Cite
|
Sign up to set email alerts
|

Anti-haemolytic and cytogenotoxic potential of aqueous leaf extract of Annona muricata (L.) and its bio-fabricated silver nanoparticles

Abstract: Nanotechnology is widely gaining worldwide application in biology and medicine because of its proven efficacy. Annona muricata contains bioactive phytochemicals with an inherent ability to bio-fabricate metal ions nanoparticles (NPs). Annona muricata aqueous leaf extract and its green bio-fabricated silver nanoparticles were evaluated on red blood cells (RBC) for anti-haemolytic activity and cytogenotoxicity on Allium cepa cells. The effects of A. muricata extract (Am-E) and its biofabricated silver nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Currently, the RBCs were subjected to Ag 2 ONPs in concentrations ranging from 1000 to 75 µg/mL. The data collected showed that the synthesized NPs were non-hemolytic at lower concentrations (17,35, and 71 µg/mL), somewhat hemolytic at 75-125 µg/mL, and hemolytic at concentrations of >125 µg/mL These findings support the earlier studies of Cichorium intybus and Annona muricata mediated Ag 2 ONPs [71,72]. Our study provided evidence that the biosynthesized Ag 2 ONPs are non-hemolytic and regarded as biocompatible at low concentrations.…”
Section: Antihemolytic Potential Of Pa-mediated Ag 2 Onps On Human Rbcssupporting
confidence: 85%
“…Currently, the RBCs were subjected to Ag 2 ONPs in concentrations ranging from 1000 to 75 µg/mL. The data collected showed that the synthesized NPs were non-hemolytic at lower concentrations (17,35, and 71 µg/mL), somewhat hemolytic at 75-125 µg/mL, and hemolytic at concentrations of >125 µg/mL These findings support the earlier studies of Cichorium intybus and Annona muricata mediated Ag 2 ONPs [71,72]. Our study provided evidence that the biosynthesized Ag 2 ONPs are non-hemolytic and regarded as biocompatible at low concentrations.…”
Section: Antihemolytic Potential Of Pa-mediated Ag 2 Onps On Human Rbcssupporting
confidence: 85%
“…According to reports, P. amarus exhibits numerous medicinal properties, including antihepatitis, antimalarial, anticarcinogenic, antiasthmatic, antiviral, antibacterial, antidiarrheal, hepatoprotective, anti-inflammatory, and antidiabetic properties (Ogunmoyole et al, 2020 ; Olorunnisola et al, 2021 ). Additionally, the use of Annona muricata is well-documented for addressing conditions such as cancer, fever, hemolysis, respiratory illness, malaria, gastrointestinal problems, liver, heart, and kidney affections, hypoglycemia, hypotension, and cancer (Gavamukulya et al, 2017 ; Badmus et al, 2022 ). Despite the various medicinal values of these plants, there is a dire need to address the challenges posed by the effects of storage methods and time on their nutraceutical values.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the literature abounds with information on the advantages of using different types of metal nanoparticles synthesised using plant extracts in therapy, making phytosynthesis a promising and sustainable alternative to conventional chemical or physical methods (Azeez et al 2020;Naikoo et al 2021;Shelembe et al 2022). These nanostructured phytocomplexes are also only toxic at extremely high concentrations, doses which are not currently used for therapeutic purposes (Badmus et al 2022).…”
Section: Introductionmentioning
confidence: 99%